Water quality modeling of the São Joaquim stream, Brazil - Gonçalves, Julio Cesar de Souza Inácio; Esposto, Murilo Senhuki (Ciência e Natura, 2019)
Water quality modeling is applied as a supporting tool for water quality management. It is useful in identifying environmental impacts from pollutants discharged into rivers and in predicting self-depuration capacity. This study aimed to simulate the water quality along a stretch in São Joaquim stream basin, in order to identify the main polluting sources in the stream and to propose measures to control pollution. The mathematical model, based on the mass balance in plug flow reactor, was implemented in an electronic spreadsheet. The modeling process involved the following stages: collecting the input data, calibration, sensitivity analysis, uncertainty analysis, and the generation of the scenarios. The calibration of the model has generated r2 above 0.68, and it was the indication that the model can explain most of the variance found in the measured data. The wastewater and the stream flow were considered the most sensitive parameters in the model. The uncertainty analysis has shown the probability of the dissolved-oxygen to be higher than or equal to 2 mg L-1, the minimum value allowed for the class 4, is 5.3 %. The main pollution sources in stream are the discharge of untreated domestic wastewater from São Joaquim City, and the surface runoff from the agricultural area. The study has shown that a wastewater treatment station must installed in the basin, in order to remove at least 93% of the organic matter currently discharged in the stream.